Intraocular pressure rise in subjects with and without glaucoma during four common yoga oositions - Jasien, Jessica V.; Jonas, Jost B. (PLOS ONE, 2015)
Purpose To measure changes in intraocular pressure (IOP) in association with yoga exercises with a head-down position. Methods The single Center, prospective, observational study included 10 subjects with primary open-angle glaucoma and 10 normal individuals, who performed the yoga exercises of Adho Mukha Svanasana, Uttanasana, Halasana and Viparita Karani for two minutes each. IOP was measured by pneumatonometry at baseline and during and after the exercises. Results All yoga poses were associated with a significant (P<0.01) rise in IOP within one minute after assuming the yoga position. The highest IOP increase (P<0.01) was measured in the Adho Mukha Svanasana position (IOP increase from 17±3.2 mmHg to 28±3.8 mmHg in glaucoma patients; from 17±2.8 mmHg to 29±3.9 mmHg in normal individuals), followed by the Uttanasana position (17±3.9 mmHg to 27±3.4 mmHg (glaucoma patients) and from 18±2.5 mmHg to 26±3.6 mmHg normal individuals)), the Halasana position (18±2.8 mmHg to 24±3.5 mmHg (glaucoma patients); 18±2.7 mmHg to 22±3.4 mmHg (normal individuals)), and finally the Viparita Kirani position (17±4 mmHg to 21±3.6 mmHg (glaucoma patients); 17±2.8 to 21±2.4 mmHg (normal individuals)). IOP dropped back to baseline values within two minutes after returning to a sitting position. Overall, IOP rise was not significantly different between glaucoma and normal subjects (P = 0.813), all though glaucoma eyes tended to have measurements 2 mm Hg higher on average. Conclusions Yoga exercises with head-down positions were associated with a rapid rise in IOP in glaucoma and healthy eyes. IOP returned to baseline values within 2 minutes. Future studies are warranted addressing whether yoga exercise associated IOP changes are associated with similar changes in cerebrospinal fluid pressure and whether they increase the risk of glaucoma progression. Trial Registration ClinicalTrials.gov #NCT01915680
Gesehen am 20.09.2017